MINERALOGIC AND THERMOBAROGEOCHEMICAL CRITERIA OF MIXING OF MAFIC AND GRANITIC MELTS (AS ILLUSTRATED BY THE HYBRID DIKES OF THE ALICHUR PLUTON, SOUTHERN PAMIRS) - Vladimirov A.G.; Titov A.V.; Chupin V.P. (My University, 1990)
For understanding the role of mixing processes in gabbro-granite magmatism, postgranitic dikes of lamprophyre and diorite porphyry are especially interesting because mineralogic criteria of both mafic and granitic rocks are combined in them. Here we shall analyze a mixing model for the hybrid dikes of the Alichur monzodiorite-granite pluton, southern Pamirs. The petrography of this diorite porphyry clearly indicates that it is hybrid. It is a dense gray-green rock with a groundmass converted to a sericite-chlorite aggregate. The phenocrysts are minerals of two genetically different groups: magmatic proper and and xenogenic. The overall effect of contamination at depth cannot be evaluated, nor can the primary composition of mafic magma be estimated. Let us emphasize merely that the hybrid diorite porphyry studied is similar in bulk composition to the monzonites of the early intrusive phases of the Alichur pluton. Therefore, the above processes of repeated mixing of melts of contrasting composition very likely could have played a major role in the emplacement of such monzonites.